Jewish Libraries and Archives in America - Berger, Pearl (Judaica Librarianship, 2006)
In celebration of the occasion of the 350th anniversary of Jewish immigration to America, this paper takes a look back and then looks forward, highlighting both achievements and challenges in the realms of Jewish libraries and archives as well as their associated professions. The paper scans the past fifty years, since the tercentenary in 1954, pointing to evidence of much growth and expansion. It then proceeds to discuss areas of development for the future, taking into account opportunities presented by the digital age.